Cognitive constraints and economic incentives - Francesco D'Acunto; Daniel Hoang; Maritta Paloviita; Michael Weber (Bank of Finland, 2023)
Unique administrative data on a representative population's cognitive abilities, spending, and financials reveal that consumers at or below median cognitive abilities barely react when their incentives to spend or borrow change, even if they earn high incomes and are financially unconstrained and conditional on formal education, personal and macroeconomic expectations, and rich demographics. Matched survey-based data on this population show that non-responsive consumers fail to grasp how the incentives to consume, save, and borrow change over time. Cognitive constraints limit the effectiveness of policies targeting household consumption and debt and might lead to regressive redistribution from low- to high-cognitive-ability consumers.
Keywords: D12; D91; E21; E52; G41; G51; 330; Behavioral Economics; Limited Cognition; Consumption; Borrowing; Heterogeneous Agents; Redistribution; Inequality